A grounded theory based kano model to develop age-friendly housing retrofit strategies for older people in China - Erxin Tu; Ying Zhou (Journal of Asian Architecture and Building Engineering)
China’s aging population is rapidly growing, with home-based care becoming the preferred choice for many older adults. Age-friendly housing (AFH) is a key measure to improve their quality of life, yet a systematic decision-making framework remains lacking. This study develops a Grounded Theory-based Kano Model to prioritize AFH design strategies for different older adult groups. The results indicate that strategies related to mobility impairments have the highest priority, followed by those addressing external assistance, physical adjustments, vision, fine motor skills, and hearing loss. Different age groups show varied needs for mobility support and environmental visibility. Men place higher priority on eliminating indoor height differences and providing support than women. Older adults living alone or with caregivers have lower priorities for several design strategies. Those with arthritis, cerebrovascular diseases, or sensory impairments have greater demands for walking safety and communication-related modifications. The study reveals a direct link between design strategy priorities and physiological decline, providing empirical data for AFH design prioritization. These findings offer a basis for optimizing AFH retrofit subsidy policies for older adults with varying physical abilities and for cities at different economic levels.